2012
DOI: 10.1007/s12253-011-9493-5
|View full text |Cite
|
Sign up to set email alerts
|

D-Dimer as a Potential Prognostic Marker

Abstract: Malignant tumors are often accompanied by increased risk for procoagulant activity, thrombosis and embolism. As a marker indicating such disturbancies is D-dimer, a product of fibrinolysis. In this retrospective study almost 300 patients with malignant tumors were evaluated. During LMWH treatment (as thromboprophylaxis) the highest frequency of VTE with worst prognosis occurred in pancreatic cancer (partly due to the late discovery) followed by ovarian, colonic and breast cancers. Also, increased D-dimer level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…Besides, a number of studies have confirmed the predictive value of D-dimer levels for venous thromboembolism (16). This study found that FIB levels were increased in CRC patients, especially in those with T2DM.…”
Section: In Colorectal Cancer Patientssupporting
confidence: 68%
See 1 more Smart Citation
“…Besides, a number of studies have confirmed the predictive value of D-dimer levels for venous thromboembolism (16). This study found that FIB levels were increased in CRC patients, especially in those with T2DM.…”
Section: In Colorectal Cancer Patientssupporting
confidence: 68%
“…D-dimer is an end-product of FIB and crosslinked fibrin degradation. It appears in the blood as a small peptide fragment after the activation of the fibrinolytic system and also signals the activation of coagulation (16).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it could be accepted as a potential prognostic marker. 10,11 The aim of this study was investigation of prognostic value of D-dimer in non-metastatic breast cancer patients without thromboembolism.…”
Section: Introductionmentioning
confidence: 99%
“…There were plenty of articles working on the relation between D-dimer and cancer [11,25]. Han et al demonstrated the significant association between elevated D-dimer concentrations and the possibility of occult cancer in patients with unprovoked venous thromboembolism (VTE) [26].…”
Section: Discussionmentioning
confidence: 99%